Pilot-scale hydrogen generation from the hydrolysis of black aluminum dross without any catalyst. (February 2022) - Kale, Mehmet; Yılmaz, İbrahim Halil; Kaya, Abdulaziz; Çetin, Ali Emrah; Söylemez, Mehmet Sait
Abstract: This study presents a sustainable method for the production of hydrogen gas without adding any catalyst from the hydrolysis of black Al dross. A pilot-scale experimental setup consisting of a reactor, a condenser, and control and measurement devices was constructed to perform chemical reactions and physical measurements. The dross used in experiments was not activated by any process and can be found in facilities (Al production plants or die casting factories) with a grain size lower than 400 μm. The chemical composition revealed by XRF showed that the black dross contained 41.96% Al. Major and minor crystalline phases present in the sample were detected by XRD. A set of experiments was performed to investigate the effects of gravimetric dross to water ratio, pH value, initial water temperature, the pressure of the reaction mixture in time for H2 synthesis. 120 L of gas were maximally produced after reacting 1 kg of Al dross with 2 kg of hot tap water at 100 °C. The H2 purity of the gas mixture and the calorific value of the mixture were respectively measured by gas chromatography and gas calorimeter as 93.24% and 2375 kcal/m 3 . After hydrolysis of the Al dross, XRD, SEM, and EDX analyses revealed the formation of hydrolysis products and their morphology. This showed that the resultant mixture tends to become harmless and can be used for various fields of the industry as a by-product. Graphical abstract: Image 1 Highlights: Characterization of black dross reveals the chemical mechanism and hydrogen yield. Hydrogen evolves from the hydrolysis of black dross without any catalyst. Increasing the gravimetric dross-to-water ratio shortens the induction time. Water unavailability influences the reaction mechanism adversely. Increasing the mixture temperature and pressurization improves the reaction kinetics.